Students' Climate Change Literacy: Implementing RBL-STEM Makerspace Materials on Recycling Plastic Waste into Ecobricks - Prastiti, Tri Dyah; Novianti, Idha; Wahyuningrum, Endang; Dafik, Dafik; Ridlo, Zainur Rasyid; Mursyidah, Indah Lutfiatul; Safiati, Okti Anis (Universitas Pendidikan Mandalika, 2026)
Climate change is an increasingly significant concern due to rising sea levels and extreme weather events. This phenomenon has made specific regions uninhabitable or unsuitable for agriculture. In addition, promoting climate change literacy is one of the key factors in addressing the posed challenges. Therefore, this research aimed to analyze the implementation of Research-Based Learning with Science, Technology, Engineering, and Mathematics (RBL-STEM) materials to promote students' climate change literacy, using a mixed-methods design. This research employed a mixed-methods design. Quantitative methods were used to analyze climate change literacy, while qualitative methods examined learning activities and phase portraits under the implementation of the materials. The two classes used comprised a control class of 40 students and an experimental class of 42 students. Meanwhile, the instruments used were interviews, questionnaires, and students’ climate change literacy tests. The results showed that there were differences between the control and experimental classes using an independent sample t-test with a sig value (2-tailed) of 0.0048 (<0.05). In the context of this research, the implementation of the materials promoted students’ climate change literacy in recycling plastic waste into ecobricks.